Community-Based Education and Regional Culture, Has It Been Put into Practice? - Mohammad Fauziddin; Suryanti Suryanti; Wiryanto Wiryanto (AL-ISHLAH: Jurnal Pendidikan, 2022)
Communities and regional potential are the closest relations in the environment. The diversity and uniqueness of each community and region should be used to encourage the nation’s intellectual life. Using a literature review approach, this study aimed to obtain the appropriate strategy for implementing community-based education and local culture. Data were collected from previous research journals from 2010 to 2021. Then, it was analyzed using data reduction steps, data presentation, and conclusions or verification. The result shows that the implementation of these education approaches needs attention to the strategy and factor that affects it. The implications of the research results are discussed further in this article.